Legal Interpreter for the Jury: The Role of the Clerk of the Court in Spain - Mar Jimeno-Bulnes; Valerie P. Hans (Oñati Socio-Legal Series)
The Clerk of the Court (secretario judicial) in Spanish provincial courts is an important legal actor in the proceedings of the modern Spanish jury, introduced in 1995. In contrast to the general verdicts of traditional common-law juries, Spanish juries must answer an often lengthy list of specific questions, and must provide the reasoning supporting these responses. Early on, many Spanish juries found the task of providing legally acceptable responses and reasons challenging. Because the law permits the clerk to enter the deliberation room to assist the jury in its writing of the verdict, the clerk has come to act as a principal intermediary between the formal demands of the law and lay citizens serving on the jury. The purpose of the present study is to analyze the role of the Clerk of the Court in Spanish jury proceedings, including the jury selection phase and the verdict writing process. Drawing on interviews with Clerks of the Court, we find that clerks’ views of appropriate intervention and clerks’ practices differ significantly across jurisdictions.